Screening Trafficking : Prudent and Perilous - Hashamova, Yana (Book collections on Project MUSE., 2018)
"The book examines film and media representations of the social, political, and economic issue of human trafficking, one of the most dramatic challenges of today's globalized world. Hashamova productively combines fieldwork in NGOs in southeastern Europe, social science data, and the analysis of Western and East European anti-trafficking films and media, and their reception in the United States and the Balkans. Her book identifies a disconnect between the global flow of trafficking images and their local comprehension. The critical analysis of documentaries, feature films, video clips, and NGOs' media materials and the responses they elicit from spectators reveals the flaws of these products and the ideological structures present both in them and in their audiences."--Dust jacket.